The Influence of Population, Exports, and Regulatory Quality on Economic Growth in ASEAN Developing Countries - Meling Malida; Marselina Marselina (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of population, export and regulatory quality on economic growth in 5 ASEAN developing countries for the 2015-2020 period. The analysis technique used is Multiple Regression Analysis with the Ordinary Least Square (OLS) method with the FEM model. The results in this study indicate that partially population has a negative and significant effect on the economic growth of ASEAN countries for the 2015-2020 period, exports have a positive and significant effect on the economic growth of ASEAN countries for the 2015-2020 period, and the regulatory quality has a positive and no effect significant to the economic growth of ASEAN countries in the 2015-2020 period. Then collectively population, exports, and the regulatory quality have a significant effect on the economic growth of ASEAN countries for the 2015-2020 period.